Effect of Feeding Moringa (Moringa oleifera) as Green Fodder on Feed Intake, Milk Yield, Microbial Protein Synthesis and Blood Profile in Crossbred Cows - Shankhpal, Sachin; Waghela, Chanchal; Sherasia, Pankaj; Sridhar, V; Srivastava, A K; Singh, Digvijay (Indian Journal of Animal Nutrition, 2019)
To evaluate the effect of feeding Moringa (Moringa oleifera) as green fodder on feed intake, milk yield, microbial protein synthesis, and blood profile, a study was conducted on twenty lactating crossbred cows in Anand district of Gujarat. Cows were divided into two groups of ten each, based on milk yield (9-10 kg/d), fat (3.5-3.8%) and stage of lactation (30-100 days in milk). Cows in control group were fed 3.0 kg each chaffed wheat and pulse straw, 15.0 kg green hybrid napier and 5.0 kg cattle feed (23.0% CP; 4.0% EE). Whereas, cows in experimental group were fed 15.0 kg Moringa green fodder (by replacing 15.0 kg hybrid napier) for 90 days. Nutrient requirement was adjusted by reducing quantity of cattle feed (3.5 kg). Study revealed that milk yield and fat percent increased (P